Understanding the drivers of a pro-environmental attitude in higher education institutions: the interplay between knowledge, consciousness, and social influence - Sehar, Aqsa; Orangzab,; Akbar, Minhas; Poulova, Petra; Vasudevan, Asokan; Huang, Tianjiao (Frontiers in Environmental Science, 2025)
Academicians with a pro-environmental attitude can play a pivotal role in developing curricula and new programs aimed at education for sustainable development. Therefore, it is of utmost importance to identify the factors that influence academicians’ positive attitude toward the environment. This study attempts to investigate the effects of environmental consciousness, environmental knowledge, and biospheric values, as well as the moderating effects of social influence, on the attitude toward the environment among the faculty members of higher education institutions (HIEs) in Southern Pakistan. The data were collected from six universities in the district of Vehari, Punjab, Pakistan. After checking for reliability and validity, the study used the structural equation modeling technique to examine the aforementioned association. The results reveal that environmental consciousness and biospheric values significantly influence the attitude of faculty members toward the environment. Furthermore, social influence positively moderates the relationship only between biospheric values and attitudes toward the environment. Overall, this study contributes original insights into the factors influencing pro-environmental attitudes among faculty in a specific cultural and educational context. Its findings can inform targeted strategies to enhance environmental education and engagement in higher education, making it a valuable addition to the literature on education for sustainable development. The findings could guide policymakers of higher education institutions in promoting a pro-environmental attitude among faculty members by implementing awareness programs that increase environmental consciousness and integrate biospheric values into their core mission. Furthermore, HEIs should also establish “green teams” to induce a positive environmental attitude through social influence.